1989
DOI: 10.1007/bf02726607
|View full text |Cite
|
Sign up to set email alerts
|

A simple field test for identification of night-blindness

Abstract: A simple and replicable field test to measure dark adaptation time has been developed. It required a darkened room with a 5 watt bulb covered with a piece of black cloth, a spherical white object of 22 cm diameter suspended vertically from a horizontal string, a stool, a black curtain, a Maxwell electronic photographic flash unit and a stop-watch. The spherical object behind the closed curtain was hung 1.5 m away from the subject either to his left or right, or in the centre of the room. The seated subject was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This finding is also in agreement with studies of serum vitamin A levels in other areas with a high prevalence of night blindness. For example, a study in India (19) showed that the mean serum vitamin A level among children who were not night blind was 17.5 pg/dl, while in Indonesia 45% of children reported not to be night blind and who did not have A. Hussain et al…”
Section: Methodsmentioning
confidence: 99%
“…This finding is also in agreement with studies of serum vitamin A levels in other areas with a high prevalence of night blindness. For example, a study in India (19) showed that the mean serum vitamin A level among children who were not night blind was 17.5 pg/dl, while in Indonesia 45% of children reported not to be night blind and who did not have A. Hussain et al…”
Section: Methodsmentioning
confidence: 99%